Fabrication of Bacterial Cellulose Nanofibers/Soy Protein Isolate Colloidal Particles for the Stabilization of High Internal Phase Pickering Emulsions by Anti-solvent Precipitation and Their Application in the Delivery of Curcumin - Shen, Rui; Lin, Dehui; Liu, Zhe; Zhai, Honglei; Yang, Xingbin (Frontiers in Nutrition, 2021)
In this work, anti-solvent precipitation and simple complex method were applied for the preparation of bacterial cellulose nanofibers/soy protein isolate (BCNs/SPI) colloidal particles. FTIR showed that hydrogen bonds generated in BCNs/SPI colloidal particles via anti-solvent precipitation were stronger than those self-assembled by simple complex method. Meanwhile, the crystallinity, thermal stability, and contact angle of BCNs/SPI colloidal particles via anti-solvent precipitation were improved as compared with those of BCNs/SPI colloidal particles via simple complex method. BCNs/SPI colloidal particles via anti-solvent precipitation showed a better gel viscoelasticity confirmed by dynamic oscillatory measurements. Furthermore, high internal phase Pickering emulsions (HIPEs) stabilized by BCNs/SPI colloidal particles via anti-solvent precipitation were more stable. Since then, the HIPEs stabilized by BCNs/SPI colloidal particles via anti-solvent precipitation were used for the delivery of curcumin. The curcumin-loaded HIPEs showed a good encapsulation efficiency and high DPPH removal efficiency. Additionally, the bioaccessibility of curcumin was significantly increased to 30.54% after encapsulation by the prepared HIPEs. Therefore, it can be concluded that anti-solvent precipitation is an effective way to assemble the polysaccharide/protein complex particles for the stabilization of HIPEs, and the prepared stable HIPEs showed a potential application in the delivery of curcumin.